Synthesis and Antimicrobial Action of 1,2,4-Triazole Derivatives Containing Theophylline and 1,3,4-Thiadiazole Fragments In their Structure - Zvenihorodska, Т.; Hotsulia, A.; Kravchenko, S.; Fedotov, S.; Kyrychko, B.; Гоцуля, Андрій Сергійович; Федотов, Сергій Олегович (My University, 2021)
1,2,4-triazole derivatives display a wide range of biological properties, such as antimicrobial, antimycotic, antiviral and other ones. Synthesis of new 1,2,4-triazole derivatives is a very relevant approach as this heterocyclic system is low toxic and pharmacologically active. This prompted us to synthesize in one structure a heterocycle with theophylline and 1,3,4-thiadiazole fragments and to study their biological properties further. This work presents our studies of the antimicrobial activity of the synthesized compounds Piperazin-1-ium 2-((5-((theophylline-7-yl)methyl)-4-ethyl-1,2,4-triazol-3-yl)thio)acetate (GKP-F-67) and Piperazin-1-ium 2-(((4-phenyl-5-(((5-(phenylamino)-1,3,4-thiadiazol-2-yl)thio)methyl)-4H-1,2,4-triazol-3-yl)thio)acetate (GKP-245). Estimation of the minimum inhibitory concentration of the synthesized compounds was carried out with the method of serial dilution in the Mueller-Hinton Broth inoculated with 1 ml of the microorganism under study. The presence or absence of visible growth was evaluated after incubation. 6-hour broth cultures of the microorganisms under study were used for the preparation of the inoculum. The concentration of the microbial suspension was equivalent to the 0.5 McFarland turbidity standard. As test cultures we used 18-hour agar or broth cultures of museum strains of S.aureus ATCC 25923, E.coli ATCC 25922, E.faecalis ATCC 29212, C.albicansCCM 885 and clinical strains of P.haemolytica, Enterobacter spp., Proteus spp., Staph. spp., S.pyogenes. Microorganisms were considered sensitive to the test compounds if the inhibitionzone was larger than 10 mm. The minimum inhibitory concentration of GKP-F-67 and GKP-245 solutions was 750 mkg/ml formost microorganisms tested. The best antimicrobial activity of GKP-F-67 and GKP-245 solutions was exhibited at concentrations of 1% and 3%.
Keywords: 1,2,4-triazole; theophylline; 1,3,4-thiadiazole; microorganisms; antimicrobial action